Youth participation on social networks: purposes, opportunities and rewards - García Galera, María del Carmen; Alonso Seco, José; Del Hoyo Hurtado, Mercedes (Anàlisi, 2013)
Among the multiple applications and tools provided by the Internet, social networks have become a reference point for citizen participation since they enhance the possibility of being informed and to inform in an easy, fast and massive way. These tools also have the capacity to drive social, civic and/or political mobilization. Against those critics who consider social networks as a place full of dangers, there are studies that explain how social networks are in fact a meeting place, a space for debate, for business, and ultimately, for participation.This article presents the real possibilities of social networks for young people, mainly focusing on the perception of them as a platform to extend their offline social relationships as well as for their participation on social and/or civic events. It seeks to understand the different uses young people do of social networks, the options and opportunities offered to them, as well as the rewards that this sector of the population, as primary users, get for their participation in social networks. According to Livingston, social networks are a potential source of risk but also of opportunities mainly related to social, civic and even political participation of youth through both the virtual world and real live. The digital environment in which we live and particularly, the online social networks, can provide new opportunities for learning, participation, creativity and communication. (Livinsgtone y Haddon, 2009: 15)